ЛІНГВОСТИЛІСТИЧНІ ОСОБЛИВОСТІ МУЛЬТИПЛІКАЦІЙНОГО ФІЛЬМУ. КУЛЬТУРОЛОГІЧНИЙ, МОВОЗНАВЧИЙ ТА ПЕРЕКЛАДОЗНАВЧИЙ АСПЕКТИ - Косенко, Анна Володимирівна; Беженар, Ірина Володимирівна; Хрептик, Христина Зіновіївна (My University, 2025)
The relevance of the study is due to the fact that modern film discourse is constantly developing and requires in-depth research. The purpose of the article is a comprehensive linguistic and cultural analysis of the features and methods of transmitting individual lexical and stylistic units in animated film discourse. It is proven that there is a growing interest in the field of study of animated film discourse and its components. It is noted that the study of animated film discourse from the point of view of the components reflected in it, namely film scripts and their translations, is promising. As a result of the study, it was concluded that the key antithesis is “good-evil”, which is represented by the opposition “plant” – “trash”. The authors of the animated film the dichotomy of the world, in which the main value is life as a spiritual existence. This dichotomy gradually crystallizes in the process of unfolding the plot, demonstrating the diversity and contradictions of the world, the presence and absence of true life in its various manifestations, where everything that does not contribute to the prosperity of spirituality is meaningless. During the analysis of the translation of the cartoon "Wally" from English into Ukrainian, it became obvious that the number of lexical and semantic adaptations used in the translation is different. After analyzing the theoretical material, it was concluded that animated film discourse is a complex, dynamic process of interaction between the author and the recipient, which takes place in the intercultural space using the means of film language. Film discourse is expressed using verbal, nonverbal signs in accordance with the intention of the collective author; it is recorded on a material medium and is intended for reproduction on the screen and audiovisual perception by viewers. The viewer actively participates in the creation of meaning, that is, he is an active, not a passive party, and the animated film discourse is open to knowledge and allows for a large number ofinterpretations.
Косенко, А. В., Беженар, І. В., Хрептик, Х. З. Лінгвостилістичні особливості мультиплікаційного фільму: культурологічний, мовознавчий та перекладознавчий аспекти // Вісник науки та освіти. Серія «Філологія». – 2025. – № 5(35). – С. 463–472. – DOI: https://doi.org/10.52058/2786-6165-2025-5(35).
Keywords: кінодискурс, мультиплікаційний кіно дискурс, фільмоніми, аудіовізуальний переклад, калькування, перекладацькі трансформації, ономастика.; film discourse, animated film discourse, filmonyms, audiovisual translation, tracing, translation transformations, onomastics.